Nuclear channel system in secretory endometrium in natural cycle and after estradiol-progesterone substitution in transmission electron microscopy - Novotný, Radko; Oborná, Ivana; Fingerová, Helena; Lichnovský, Václav (Acta medica martiniana, 2004)
The objective of the study was to ascertain if the estradiol-progesterone substitution used for the preparation of endometrium which has been shown to elicit supraphysiological levels of circulating progesterone may also induce demonstrable changes in the ultrastructural morphology of human secretory endometrium which is characterised by three progesteron- dependent structures, the so called postovulatory triad: nuclear or nucleolar channel system, giant mitochondria and subnuclear glycogen. The study was approved by the institutional Ethic Committee and included 24 patients of one IVF centre who signed informed consent. Two sequentional endometrial biopsy specimens were taken on the 5th and 7th day after ovulation in one natural cycle and on the 5th and 7th day after the initiation of progesterone addition in another substituted cycles in the same patient. The surface and glandular epithelial cells were examined under transmission electron microscope (TEM). The appearance of nuclear channel system (NCS), giant mitochondria and glycogen was the same in both natural and substituted cycles, without abnormalities and deformations. Cells with NCS were found, mostly in clusters on discrete parts, in 55 to 70 % of ultrathin sections. The relative number of NCS positive specimens was not statistically different between the cycles or between the day +5 and the day +7 within different type of cycle. Some NCS positivity was detected more often (in 79 % and 66 %, resp.) in substituted cycles than in spontaneous ones. The percentage of NCS positive cells was also higher (median 17 % and 12 %, resp.) in substituted cycles but the differences were not statistically significant. With some caution regarding the inherent limited reproducibility of the TEM findings we can conclude that the oral hormonal substitution used in our setting does not markedly alter endometrial ultrastructural morphology.
Keywords: Endometrium; dospělí; mitochondrie; endometrium; lidé; iontové kanály; Female; Ion Channels; Estradiol; Receptors, Progesterone; receptory progesteronu; Mitochondria; Adult; ženské pohlaví; estradiol; Humans